PERAN INTERNATIONAL LABOUR ORGANIZATION DALAM MEMBANTU LAPANGAN PEKERJAAN DI ACEH PERIODE 2012-2017 - Hanafi Nurbudi Utomo, - (2018)
Unemployment that grew from year-over-year in Indonesia especially in Nangroe Aceh Darussalam became a continuous problem to its people. The Government of Indonesia builds cooperation with the ILO, an international agency focused on employment, this study aims to analyze and learn about the role of the ILO towards creating employment in Aceh for the period 2012-2015. This skew is qualitative. The type of research used are applied and descriptive. The data sources used are primary data and secondary data from interviews and literature study, as well as data modeling and planning of national decent work programs in Indonesia derived from the Ministry of Manpower and the ILO organization. The data will be analyzed by using the theory of International Organization, Employment Concept and Role Concept. Based on the analysis data, it can be concluded that ILO and GOI collaborations are providing assistance to Indonesia including in Aceh in creating employment and also improving the quality of the workforce, to improve the welfare of the people in Aceh where if more people are working then the possibility of welfare in the area will definitely increase.